2011
DOI: 10.2967/jnumed.111.094458
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Response to Treatment with Erlotinib in Advanced Non–Small Cell Lung Cancer Using 18F-FDG and 3′-Deoxy-3′-18F-Fluorothymidine PET

Abstract: The purpose of this study was to evaluate the relevance for the prediction of clinical benefit of first-line treatment with erlotinib using different quantitative parameters for PET with both 18 F-FDG and 39-deoxy-39-18 F-fluorothymidine ( 18 F-FLT) in patients with advanced non-small cell lung cancer. Methods: Data were used from a prospective trial involving patients with untreated stage IV non-small cell lung cancer. 18

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 23 publications
5
49
0
1
Order By: Relevance
“…1 and 2). Recent animal and preliminary clinical studies have suggested that 18 F-FLT may be more sensitive than 18 F-FDG for assessing tumor response (Troost et al, 2010;Kahraman et al, 2011). Our present findings indicate that 18 F-FDG and 18 F-FLT have comparable sensitivities for detecting early changes in tumor cell activity after combined YM155 and rituximab treatment in a B-NHL xenograft model (Fig.…”
Section: Combination Effect Of Ym155 With Rituximab In B-nhl 181supporting
confidence: 67%
“…1 and 2). Recent animal and preliminary clinical studies have suggested that 18 F-FLT may be more sensitive than 18 F-FDG for assessing tumor response (Troost et al, 2010;Kahraman et al, 2011). Our present findings indicate that 18 F-FDG and 18 F-FLT have comparable sensitivities for detecting early changes in tumor cell activity after combined YM155 and rituximab treatment in a B-NHL xenograft model (Fig.…”
Section: Combination Effect Of Ym155 With Rituximab In B-nhl 181supporting
confidence: 67%
“…Van Baardwijk et al (5) demonstrated heterogeneity in the metabolic response of 23 patients early during radical RT, particularly between responders and nonresponders (5). Other studies of advanced NSCLC and molecularly targeted anticancer agents (erlotinib) have also shown that early PET response with 18 F-FDG and 18 F-FLT are associated with improved progressionfree survival (21,22). However, as a targeted therapy, this response may reflect a pharmacodynamic read-out of reducing signaling through the oncogenic pathway rather than a direct measure of cell death.…”
Section: Discussionmentioning
confidence: 99%
“…We retrospectively reviewed the data of 30 patients with advanced-stage NSCLC who were enrolled between September 2007 and September 2009 into the trial at the University Hospital of Cologne [5]. The trial was approved by the local ethics committee, the responsible Federal Institute for Drugs and Medical Devices (BfArM), the responsible federal state authorities of North RhineWestphalia and the Federal Office for Radiation Protection (BfS; clinical trials NCT00568841).…”
Section: Patients and Treatmentmentioning
confidence: 99%
“…The software used was developed in-house at the VU University Medical Center Amsterdam, The Netherlands, and makes use of the 3-D search algorithm in the IDL software package version 6.2 (Interactive Data Language; Research Systems, Boulder, CA) [9,10]. The following SUV values were obtained in all studies: the maximum SUV (SUV max ), the 2-D peak SUV (SUV 2Dpeak ), the 3-D peak SUV (SUV 3Dpeak ), the 3-D isocontour at 41 % of the maximum pixel value adapted for background (SUV A41 ), the 3-D isocontour at 50 % of the maximum pixel value (SUV 50 ) and the 3-D isocontour at 50 % adapted for background (SUV A50 ) [5]. First, SUV max normalized to body weight was determined for each lesion, using the voxel with the maximum uptake.…”
Section: Pet Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation